Adolescent Marathon Training: Prospective Evaluation of Musculotendinous Changes During a 6‐Month Endurance Running Program. (29th September 2022) - DeJong Lempke, Alexandra F.; Willwerth, Sarah B.; Hunt, Danielle L.; Meehan, William P.; Whitney, Kristin E.
Abstract : Objectives: Assess changes in lower extremity musculotendinous thickness, tissue echogenicity, and muscle pennation angles among adolescent runners enrolled in a 6‐month distance running program. Methods: We conducted prospective evaluations of adolescent runners' lower extremity musculotendinous changes at three timepoints (baseline, 3 months, and 6 months) throughout a progressive marathon training program. Two experienced researchers used an established protocol to obtain short‐ and long‐axis ultrasound images of the medial gastrocnemius, tibialis anterior, flexor digitorum brevis, abductor hallicus, and Achilles and patellar tendons. ImageJ software was used to calculate musculotendinous thickness and echogenicity for all structures, and fiber pennation angles for the ankle extrinsic muscles. Repeated measures within‐subject analyses of variance were conducted to assess the effect of endurance training on ultrasound‐derived measures. Results: We assessed 11 runners (40.7% of eligible runners; 6F, 5M; age: 16 ± 1 years; running experience: 3 ± 2 years) who remained injury‐free and completed all ultrasound evaluation timepoints. Medial gastrocnemius muscle ( F 2, 20 = 3.48, P = .05), tibialis anterior muscle ( F 2, 20 = 7.36, P = .004), and Achilles tendon ( F 2, 20 = 3.58, P = .05) thickness significantly increased over time. Echogenicity measures significantly decreased in all muscles ( P ‐range: <.001–.004), and increased for the patellar tendon ( P < .001) during training. Muscle fiber pennation angles significantly increased for ankle extrinsic muscles ( P < .001). Conclusions: Adolescent runners' extrinsic foot and ankle muscles increased in volume and decreased in echogenicity, attributed to favorable distance training adaptations across the 6‐month timeframe. We noted tendon thickening without concomitantly increased echogenicity, signaling intrasubstance tendon remodeling in response to escalating distance.